Un projet pilote pour réduire les risques d’intoxication et pour prévenir la consommation excessive (Éduc'alcool, 2023)
Montréal, le 21 avril 2023 – Éduc’alcool et le Service de police de la Ville de Montréal (SPVM) ont lancé hier le projet pilote Touche pas à mon verre* en présence du ministre de la Sécurité publique du Québec, M. François Bonnardel. Cette initiative prend la forme d’une distribution gratuite de 10 000 protège-verres afin de, notamment, […]
Keywords: Bibliographie; Dans le rapport; Nettoyer

Check tes chums - Massé, Manon (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari; Jordan, Ana; Jameson, Jill; Davy, Zowie (Violence Against Women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.
Keywords: Camille

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Non-Consensual Sexual Contact at Electronic Dance Music Parties - Palamar, Joseph J.; Griffin, Marybec (Archives of Sexual Behavior, 2020)
Non-consensual sexual contact in bars is common, but few studies have focused on the extent of this problem at electronic dance music (EDM) parties, which are growing in popularity. We aimed to estimate prevalence and correlates of non-consensual sexual contact among individuals who attend EDM parties in New York City (NYC). Adults (ages 18–40 years) entering EDM parties in NYC were surveyed in 2018 using time–space sampling. Participants (n = 1005) were asked whether they had experienced unwanted or uninvited sexual contact including unwanted groping, kissing, or touching at an EDM party. We estimate that 15.2% of EDM party attendees in NYC have experienced non-consensual sexual contact at such parties. The majority (62.5%) of those reported that it occurred 1–2 times and 49.1% were usually or always drunk or high during the encounter(s). Almost all women experiencing non-consensual contact (99.5%) were all or mostly touched by men; 38.6% of men were all or mostly touched by other men. Women were at more than twice the odds of reporting non-consensual sexual contact than men (aOR = 2.38, p < .05) with 21.8% of women reporting experiencing non-consensual sexual contact compared to 11.0% of men. Among women, those ages 18–24 were at over twice the odds (aOR = 2.75, p < .05) of experiencing non-consensual sexual contact than those ages 25–40. EDM party environments can increase susceptibility to non-consensual sexual contact. Prevention needs to be geared toward those at risk, and education is needed for those likely to commit non-consensual sexual contact.
Keywords: Dance music; Drug use; Non-consensual sex; Sexual assault

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

Unwanted Sexual Attention in the Night-Time Economy: Behaviors, Safety Strategies, and Conceptualizing “Feisty Femininity” - Gunby, Clare; Carline, Anna; Taylor, Stuart; Gosling, Helena (Feminist Criminology, 2020)
Almost nothing is known about ?unwanted sexual attention? and women?s navigation of it when in bars and nightclubs. Using focus group discussions, this article addresses that gap. It develops knowledge of the behaviors that constitute unwanted, the safety strategies used to manage them, and examines how these practices underpin gender performance in night-time spaces: environments renowned for the dilemmas they pose to women. We then use these data to develop the concept ?feisty femininity? to highlight a neglected form of femininity that overtly resists unwanted encounters. This femininity can arguably play a role in efforts aimed at ending gendered violence.
Publisher: SAGE Publications

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Conceptualising safety and crime at UK music festivals: A gendered analysis - Measham, Hannah King, Fiona, Hannah Bows (Gendered Violence at International Festivals, 2020)
There has been a global surge in music festivals over the last decade, especially in Europe. In the UK, it is estimated that more than 3.5 million people attended the 230 music festivals in 2015 (Time Out, 2015; UK Festival Awards, 2016). Despite a body of research indicating higher levels of crime, particularly acquisitive and violent crime in spaces with similar characteristics (e.g. nightclubs, pubs and gigs), there have been no previous studies examining the occurrence or nature of crime at music festivals. This chapter brings together conceptual developments across the social sciences to shed light on the underexplored subject of gender and safety at music festivals, a leisure location of growing interest to social scientists and of significant growth within the events industry. This chapter presents data from the first UK study to explore safety and crime at music festivals and raises questions regarding the distinctive features of commercialised music festivals, the extent to which they can be considered transgressive or countercultural spaces and what might be the distinctions, if any, of gendered sexual violence within such spaces.
Num Pages: 18

The Role of Rape-Supportive Attitudes, Alcohol, and Sexual Arousal in Sexual (Mis)Perception: An Experimental Study - Benbouriche, Massil; Testé, Benoit; Guay, Jean-Pierre; Lavoie, Marc E. (Journal of Sex Research, 2019)
While sexual misperception does not irrevocably lead to sexual aggression, it remains a significant risk factor. The present study investigated the effects of rape-supportive attitudes, alcohol, and sexual arousal on sexual perception. We used a 2 × 2 between-participants factorial design to randomly assign 135 men from the general population to a condition with or without alcohol (blood alcohol concentration target of .08%) and to a condition with or without sexual arousal. Participants were asked to listen to an audiotape depicting a sexual interaction between a man and woman and to indicate if and when they believed the woman was no longer interested in having sex. Results, obtained through survival analyses, indicate that the effects of rape-supportive attitudes on sexual misperception are moderated by alcohol consumption. Alcohol appears to be an important situational factor for activating men's implicit theories. Our study sheds new light on the role of knowledge structures in sexual perception: It identifies when, as well as suggesting how, rape-supportive attitudes may disturb sexual perception and ultimately lead to sexual misperception.
Keywords: Adult; Alcohol Drinking; Arousal; Attitude; Female; Humans; Male; Rape; Refusal to Participate; Sexual Behavior; Survival Analysis; Tape Recording; Young Adult

Experiences and perceptions of gender in the Australian music industry - Fairlamb, Hannah Mary; Fileborn, Bianca (Perfect Beat, 2019)
This article reports results from an online survey (n=207) about experiences and perceptions of gender from those working in the Australian music industry. Taking a feminist approach, theory on gender and hegemonic masculinity is used to discuss power in a gendered context in this industry. Literature shows women and girls experience a range of difficulties in the music industry worldwide, such as negative assumptions about their skill levels. The small body of research on gender and the Australian music industry has discussed topics such as the forgetting of women in Australian popular music history. Results reported in this article show that women’s worst experiences most often related to sexual violence or unwanted sexual advances; and men’s most often related to money. Findings contribute to the field by providing gendered analysis of self-reported data in an under-researched industry.
Keywords: Australia; gender; music; music industry; popular music; sexual harassment

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

When Women Do Not Want It: Young Female Bargoers’ Experiences With and Responses to Sexual Harassment in Social Drinking Contexts - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha (Violence Against Women, 2017)
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women?s responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends? help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.
Publisher: SAGE Publications Inc

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概

Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

"Yeah, We Serve Alcohol, but … We Are Here to Help": A Qualitative Analysis of Bar Staff's Perceptions of Sexual Violence - Powers, Ráchael A.; Leili, Jennifer (Violence and Victims, 2016)
This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provider, their lack of knowledge (but eagerness to learn), and their reliance on stereotypical scenarios of sexual violence and interventions. These findings are situated in a framework for understanding barriers to bystander intervention and implications for community-based bystander programs are discussed.
Keywords: Adult; Camille; Female; Focus Groups; Helping Behavior; Humans; Interpersonal Relations; Male; Rape; Restaurants; Sex Offenses

Unwanted Sexual Attention in Licensed Venues: Considering LGBTIQ Young Adults' Experiences and Perceptions - Fileborn, Bianca (2015)
English Abstract: Sexual violence within the lesbian, gay, bisexual, transgender/transsexual, intersex and queer (LGBTIQ) communities remains largely under-researched and under-theorised. Yet, emerging research suggests that sexual violence is a significant issue within the LGBTIQ communities. Additionally, the occurrence of sexual violence and unwanted sexual attention within specific social and cultural contexts is, for the most part, insufficiently examined. This article draws on research exploring young LGBTIQ adults’ perceptions and experiences of unwanted sexual attention in licensed venues. Firstly, I consider the theoretical and conceptual underpinnings of ‘unwanted sexual attention’ as a category of analysis. I then move on to consider participants’ use of licensed venues, the particular significance of pubs and clubs to LGBTIQ young people, and their perceptions and experiences of unwanted sexual attention. Finally, I discuss the implications of these findings for theoretical and conceptual understandings of unwanted sexual attention and sexual violence.
Keywords: Camille; Gender; Género; LGBTIQ; economía nocturna; licensed venues; locales con licencia; night time economy; orientación sexual; sexual orientation; sexual violence; violencia sexual

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

“Yes, I Do but Not with You”: Qualitative Analyses of Sexual/romantic Overture-Related Aggression in Bars and Clubs - Graham, Kathryn; Wells, Samantha; Bernards, Sharon; Dennison, Susan (Contemporary Drug Problems, 2010)
Assaultive and aggressive behaviors related to sexual overtures are common in commercial drinking establishments (bars, pubs, and clubs). In this article, we examined the thematic content of 251 incidents of verbal and physical aggression related to sexual/romantic overtures documented by researcher-observers in a study of Toronto bars and clubs. Aggression was examined as it emerged in the following stages of the social interaction process: (a) sexual/romantic overtures that began aggressively; (b) initiators of sexual/romantic overtures who became aggressive later in the social interaction process; (c) aggression by targets of overtures; and (d) aggression by third parties. From these thematic analyses we identify the distinctions between predatory and genuine overtures and explore the potential role of the effects of alcohol.
Publisher: SAGE Publications Inc

Managing Physical and Sexual Assault Risk in Urban Nightlife: Individual- and Environmental-Level Influences - Kavanaugh, Philip R.; Anderson, Tammy L. (Deviant Behavior, 2009)
In this article we use interview and direct observation data to examine the experiences of young people in two Philadelphia nightlife scenes, and the ways in which they manage risk of physical and sexual assault. Our analysis reveals several environmental-level factors that shape risk exposure, as well as a number of individual-level tactics used to manage risk. Our observations are discussed in terms of their implications for developing a risk management framework that accounts for the role of individual- and environmental-level factors in shaping victimization.
Publisher: Routledge _eprint: https://doi.org/10.1080/01639620902854639